Taxonomic revision of the ornate skink (Oligosoma ornatum; Reptilia: Scincidae) species complex from northern New Zealand - Patterson, Geoff B.; Hitchmough, Rod A; Chapple, David G (Zootaxa, 2013)
Although the New Zealand skink fauna is known to be highly diverse, a substantial proportion of the recognised species remain undescribed. We completed a taxonomic revision of the ornate skink (Oligosoma ornatum (Gray, 1843)) as a previous molecular study indicated that it represented a species complex. As part of this work we have resolved some nomenclatural issues involving this species and a similar species, O. aeneum (Girard, 1857). A new skink species, Oligosoma roimata sp. nov., is described from the Poor Knights Islands, off the northeast coast of the North Island of New Zealand. This species is diagnosed by a range of morphological characters and genetic differentiation from O. ornatum. The conservation status of the new taxon appears to be of concern as it is endemic to the Poor Knights Islands and has rarely been seen over the past two decades.